Evidence of Komatiitic Basalt Enclaves in the Téra-Ayorou Pluton (Liptako, West Niger) (West African Craton) - Attourabi, Sofiyane Abdourahamane; Hallarou, Mallam Mamane; Ahmed, Yacouba; Sanda Chékaraou, Mahamane Moustapha (European Scientific Journal, ESJ, 2024)
The basic enclaves (amphibolo-pyroxenites) of the Téra-Ayorou pluton in Niger Liptako (NE portion of the Man Ridge of the West African Craton) are characterized by high MgO, low Na2O, K2O, and TiO2 contents, high CaO/Al2O3 ratios, depletion of light rare earth and enrichment in Ni and Cr. These basic enclaves are thought to come from certain basic to ultrabasic Pogwa and Ladanka plutonites in the Diagorou-Darbani greenstone belt, with which they share the same geochemical characteristics. This suggests that these enclaves were ripped out by the pluton as it was being emplaced. The basic enclaves and basic plutonites with ultrabasites have different signatures from those of the birimian basites of the West African Craton, which are tholeiitic and calc-alkaline. The amphibolo-pyroxenite enclaves of the Téra-Ayorou pluton and the basic to ultrabasic plutonites of the Diagorou-Darbani greenstone belt constitute a fairly continuous line of komatiitic rocks from peridotites (serpentinites) to basalts (metapyroxenites, amphibolites). This komatiitic lineage results from the fractional crystallization of a magmatic liquid from a mantle source with variable partial melting rates. The komatiitic line and the tholeiitic and calc-alkaline lines are closely intertwined in the field.